Flavoured sterilized milk enriched with alpha linolenic acid: physico-chemical properties and evaluation of storage stability: alpha linolenic acid enriched flavoured sterilized milk - Tambade, Pramod B; Sharma, Monika; Singh, Ashish K (Indian Journal of Dairy Science, 2025)
Milk is often referred as a complete food, but it lacks certain essential fatty acids like omega-3 fatty acids. Omega-3 fatty acids have been associated with reduced risk of several health diseases. Milk is being widely consumed throughout the masses; it would serve as an ideal vehicle for omega-3 fatty acid fortification. Flaxseed oil is one of the richest vegetarian sources of omega-3 fatty acids. However, due to high susceptibility to oxidation, the use of flaxseed oil is limited in food and dairy products. But this problem can be overcome by encapsulating flaxseed oil where a protective coat is formed on oil droplets. In the present study microencapsulated flaxseed oil was used to fortify milk. The selected microcapsule was used to fortify milk with the aim of providing 25 and 50% RDA of alpha linolenic acid in the milk. Based upon better sensory acceptability, 25% RDA level was selected for further study. Upon addition of flaxseed microcapsules, the sterilized flavoured milk samples were analysed for physico-chemical, sensory and compositional parameters. The samples were also evaluated for storage stability for 28 days. The pH and viscosity of the fortified flavoured milk samples differ significantly (p 0.05) in the flavour score of fortified and control sterilised milk samples. But on 28th day of storage there is significant (p